Correction to: Multiple functions of CREB-binding protein during postembryonic development: identification of target genes - Roy, Amit; George, Smitha; Palli, Subba Reddy (BMC genomics, 2018)
Following the publication of this article [1], the authors found that the primers listed for CREB-binding protein were not correct. This mistake occurred during assembly of the primer table and the authors apologize for this error. This correction does not change the data included in the paper, their interpretation nor the conclusions drawn.